CO2-Vadose and DEMO-CO2 Projects: Two Complementary Projects about Geochemical and Geophysical Monitoring During CO2 Leakage. (July 2017) - Garcia, B.; Rhino, K.; Loisy, C.; Le Roux, O.; Cerepi, A.; Rouchon, V.; Noirez, S.; Le Gallo, C.; Delaplace, Ph.; Willequet, O.; Bertrand, C.
Abstract: From a natural underground cavity and two locations situated in a well, three CO2 injections have been designed and performed under controlled conditions in order to study its migration along the carbonate vadose zone and to test geochemical and geophysical techniques. After the understanding of the natural CO2 dynamics and the establishment of a baseline, some numerical simulations have been performed to help to optimize the monitoring strategy (spatially and temporally). A mixture of CO2 + noble gases has been injected and the results show that CO2 subsurface leakage can be anticipated thanks to these inert chemical gases used as tracers (He + Kr). The geochemical and geophysical monitoring approaches are very complementary.